Politicization of the broadcast media: An examination of 2015 general elections in Nigeria - Bashir, Muktar; Mohd Sani, Mohd Azizuddin; Ahmad Zakuan, Ummu Atiyah (2017)
Propose - There cannot be democracy without elections, nor can there be elections without the presence of vibrant media.Therefore, the media serves as the catalyst for the smooth operation and conduct of any election.Media as a channel of communication are constitutionally responsible for steering the affairs of any electoral democracy by educating the populace with up to date information that is qualitative in nature to transform them into meaningful mindsets for the betterment of the system in general.However, the way and manner the media conducted its affairs during the 2015 general elections in Nigeria necessitated the need for this paper.Therefore, the aim of this paper is to examine the nature and character of the broadcast media specifically looking at the 2015 general elections in Nigeria.Also, the paper adopts, one of the normative theories in communication studies (Authoritarian theory of communication) to set the pace in the examination.